Evaluation of the implementation of Hydroponic Training in Order to Support the Urban Farming program in the City of Surabaya - Sri Tjondro Winarno (Nusantara Science and Technology Proceedings, 2021)
The purpose of this research is to evaluate hydroponic training so that the benefits and results of the analysis of the success of this hydroponic training program are known. Sampling from a population that is in accordance with the evaluation of hydroponic training by means of a census on all populations of training participants according to the field that we sample. The analysis used in this research is descriptive qualitative analysis, which aims to get a true picture of an object and test the truth of an opinion. The hydroponic training scoring system is based on a Likert scale rating, with 5 answer choices. From the results of the evaluation of the implementation, the results obtained with good criteria of 94.12% and very good at 5.88%. The conclusion of this study shows that this hydroponic training is very useful and supports the urban farming program in Surabaya.